Intestinal Motility after Ileal Pouch-Anal Anastomosis - Jacques Heppell (Canadian Journal of Gastroenterology)
Colectomy, mucosal proctectomy and ileal pouch-anal anastomosis, has become the procedure of choice for carefully selected patients with ulcerative colitis requiring surgery. Pathophysiological studies after the operation have led to a better understanding of the mechanisms of continence and to the development of new technology to study anorectal function. Manometric studies of the anal sphincter, ileal pouch and distal ileum have shown that the operation alters the mechanisms of continence. The maximal tolerable volume of distension of an ileal pouch often approximates that of a normal rectum and yet the functional outcome may differ from a well functioning ileorectal anastomosis. Many other factors influence the result of the operation. The influence of the pattern of motility of the proximal and distal small bowel has been evaluated. The ileal pouch accommodation to distension has been correlated to clinical outcome. Scintigraphic techniques were designed to study the relationship between motility, filling and emptying of the ileal reservoirs. Measures designed to slow intestinal transit, increase absorption and reduce stool output are under investigation.